Do E-Satisfaction and E-Trust Really Mediate Effect E-Service Quality on Repurchase Intention of Online Fashion? - Adnan Adnan; Syamsul Bahri; Hamdiah Hamdiah; Aiyub Aiyub; Muhammad Roni (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study investigates the influence of e-service quality on repurchase intention, considering the mediating roles of e-satisfaction and e-trust among consumers of Zalora.co.id in Banda Aceh. Research Methodology: A quantitative survey approach was applied, with data collected through questionnaires using purposive sampling and measured on a Likert scale. The relationships among variables were analyzed using path analysis to capture both direct and indirect effects Results: The results revealed that e-service quality does not directly affect repurchase intention. However, it significantly enhances e-satisfaction and e-trust, which, in turn, have a direct and significant impact on repurchase intention. These findings confirm that e-satisfaction and e-trust are key mediators linking e-service quality to repurchase intention. Conclusions: This study emphasizes that improving customer satisfaction and trust is essential for strengthening repurchase intentions, rather than relying solely on service quality. Limitations: This study is limited to Zalora.co.id consumers in Banda Aceh, which may constrain the broader applicability of the findings. Contributions: Theoretically, this study enriches the e-commerce consumer behavior literature by demonstrating the mediating mechanisms through which service quality influences behavioral intention. Practically, this study offers guidance for e-commerce platforms to focus on strategies that build trust and enhance customer satisfaction.